Interrogating The Role of Democracy in Providing Social Policies for People with Disabilities: Insights from Southeast Asia - Putra, Fadillah (Indonesian Journal of Disability Studies, 2018)
In developing countries the quality of life of their citizens is far from democratic principles. Many are found in public spaces that not support the existence of accessible services for persons with disabilities. Among many exclusion issues, this essay wants to focus on disability, which is related to the low attention of the government to people with disabilities' accessibility and representation. Social exclusion especially to people with disabilities strongly related to the concept of power relation. This implies that the social transformation (democratisation) will occur when the political system guarantees the power and power relations to be recognised by each individual in the society. Using "power relation" concept in Foucauldian perspective in analyzing social policy of four South East Asian governments, namely Indonesia, Malaysia, Thailand, and Philippine, this shows that there is a need for a review of the democratization process.